ET-7 EVALUATION OF HYPOXIA-TARGETING RADIOPHARMACEUTICAL64CU-ATSM FOR PET MONITORING WITH LOCAL THERAPY IN HIGH-GRADE GLIOMA MODEL. (3rd December 2022) - Yoshii, Yukie; Hihara, Fukiko; Matsumoto, Hiroki; Igarashi, Chika; Tachibana, Tomoko; Shinada, Mitsuhiro; Ming-Rong, Zhang; Oshima, Akito; Sato, Hidemitsu; Narita, Yoshitaka; Kurihara, Hiroaki; Yamamoto, Tetsuya; et al.
Abstract: World Health Organization (WHO)-defined central nervous system (CNS) grade 4 high-grade gliomas (HGGs) are highly aggressive brain cancers characterized by the presence of hypoxia within a rapidly-growing tumor mass. Due to invasion to the surrounding brain parenchyma, these tumors commonly recur locally, despite aggressive surgical resection, and new therapeutic approaches are required for local tumor control. Here, we show a positron emission tomography (PET) integrated local therapy (PETx), to target HGGs. This technique consists of a one-step local theranostic application, followed by PET monitoring, with a hypoxia-targeting radiopharmaceutical 64 Cu-diacetyl-bis ( N 4 -methylthiosemicarbazone) ( 64 Cu-ATSM). We examined the safety and therapeutic potential of 64 Cu-ATSM PETx for HGG patient-derived xenograft (PDX) tumors, which recapitulated the parent tumor phenotype of high expression of hypoxia-inducible factor-1α and BNIP3, biomarkers of tissue hypoxia. Biodistribution, dosimetry, and toxicity studies of 64 Cu-ATSM local administration determined the maximum tolerated dose (MTD) to be 3.7 MBq in mouse. PETx using the MTD dose of 64 Cu-ATSM indicated high tumor penetration, distribution, and retention of 64 Cu-ATSM in PDX tumors, as compared to sham-treated mice. The 64 Cu-ATSM PETx promoted DNA double-strand breaks, followed by apoptosis in tumors, and extensively prolonged overall survival with tolerable systemic toxicity. These findings indicate the potential of 64 Cu-ATSM PETx to induce high uptake in the hypoxic tumor microenvironment, and strong therapeutic effects in PDX models. These findings establish 64 Cu-ATSM PETx as a potential novel theranostic approach to facilitate local control of WHO CNS grade 4 HGGs.